TRIGLYCERIDE GLUCOSE INDEX AS A PREDICTOR OF SEVERITY OF CORONARY ARTERY DISEASE IN ACUTE CORONARY SYNDROME - Baligar, Dr Basavaraj; Baligar, Dr Shilpa; K, Dr Dhruvanandan; Hiremath, Dr Rajkumar (South Eastern European Journal of Public Health, 2025)
INTRODUCTION: Coronary artery disease (CAD) is a major cause of morbidity and mortality in Indian population presenting to EMD with acute coronary syndrome (ACS). TyG index which is a new parameter assessed using fasting plasma glucose and Triglyceride levels is known to predict severity of insulin resistance. This study aims at validating the hypothesis that increase in TyG index is associated with increased risk of multivessel disease. METHODS: This study was conducted in cardiology department in a tertiary care hospital KIMS in Hubballi, Karnataka, over a period of 1 year (2023-24). Triglyceride glucose index was calculated with formula: Log [Fasting triglyceride (mg/dl) X fasting plasma glucose (mg/dl) /2]. Further the severity of CAD was calculated using SYNTAX and GENSINI score which was correlated with TyG index. RESULTS: We have recruited 109 participants with CVD. The mean (SD) TyG index was 5.4 [median (IQR) -5.5 (5.0-5.8]. There was a positive correlation between TyG index and Gensini score (correlation coefficient - 0.33) similarly, a positive correlation was observed between TyG index and SYNTAX score (correlation coefficient - 0.37). The mean (SD) TyG index score was 5.1 (0.32) in SVD group and 5.6 (0.46) in participants with multi vessel diseases (p <0.001). For a TyG index cut-off of 5.4 we observed sensitivity of 80%, specificity of 72.7% with significant AUC of 0.83. CONCLUSION: Our study demonstrated that increased TyG index is associated with increased risk of multi vessel CAD. The results further demonstrated that higher TyG index is associated with more severe CAD.